Efecto de diferentes sistemas de conducción y fertilización n-p-k sobre las implicancias agronómicas en uvilla (physalis peruviana l.) - Córdova Zambrano, Juliana Lilibeth (2020)
Golden berry crop, due to its economic and nutritional importance has increased in recent years. However, little is known about methods and techniques of cultivation, as well as interactions between management systems and nutrition. In this sense, at the Experimental Station “La Argelia”, a cultivation of golden berry was installed, under a design in subdivided plots in which different management, fertilization and pruning systems were evaluated respect to some vegetative and productive variables. The treatments consisted, for the main plot in a conduction system with one and two cables. For fertilization in the subplot, three levels were applied, considering a control, in addition to fertilization based on soil analysis and a complete fertilization based on requirement plus soil analysis. While for the sub-subplot the pruning factor had two levels, one to 4 branches and the control with no pruning. The conduction system did not show significant difference for vegetative and productive variables, on the other hand, the complete fertilization and pruning favored the greater length of the shoot, diameter of the base of the main stems, weight of the fruit with and without calyx; while pruning and correction fertilization, showed an interaction for RGR, equatorial diameter and polar diameter of the fruit. Also, the cross-sectional area of the trunk showed difference for pruning factor, the estimated load showed significant difference for the complete fertilization, and was observed a higher concentration of Brix degrees for fertilization based on soil analysis. Results indicated that there are positive effects between increasing the fertilization levels on the vegetative parameters of the plants, while pruning contributed the growth vegetation, allowing a greater penetration of light, increasing the efficiency of photosynthesis and thus improving the vegetative and productive growth of plants. Keywords: golden berry, conduction system, fertilization, pruni